Penerapan Sistem Informasi Akuntansi, Tata Kelola, dan Kompetensi Manusia: Analisis Pengaruhnya terhadap Ketepatan Waktu Pelaporan Keuangan dengan Metode Regresi Data Panel - Fajrillah, Fajrillah; Zuhri, Zuhri; Almastoni, Almastoni; Tarwiyah, Tarwiyah (Journal Global Technology Computer, 2025)
This study aims to analyze the effect of Accounting Information Systems (AIS) implementation on the quality of financial reports in automotive and component sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Unlike previous studies that relied on perception data, this study utilizes secondary data sourced from company annual reports to provide more objective evidence. Financial report quality is proxied by audit delay (timeliness), while AIS is measured through the disclosure of Enterprise Resource Planning (ERP) implementation. The moderating variable, Internal Control, is proxied by the frequency of Audit Committee meetings, and HR Competence is proxied by the financial educational background of the Board of Directors. Using panel data regression analysis (via Chow, Hausman, and LM tests), the results show that companies disclosing the use of ERP-based AIS have a significantly higher level of reporting timeliness. Furthermore, moderation effect testing proves that this positive relationship between AIS and timeliness is strengthened by effective internal control and competent human resources at the director level. These findings indicate that technology requires robust governance and adequate human competence to produce quality and timely financial reports. The research implications highlight the importance of a holistic approach to technology investment, where strengthening oversight and improving HR quality must go hand in hand with information system implementation.